Advanced GeSn/SiGeSn Group IV Heterostructure Lasers. Issue 6 (27th March 2018) - von den Driesch, Nils; Stange, Daniela; Rainko, Denis; Povstugar, Ivan; Zaumseil, Peter; Capellini, Giovanni; Schröder, Thomas; Denneulin, Thibaud; Ikonic, Zoran; Hartmann, Jean‐Michel; Sigg, Hans; Mantl, Siegfried; et al.
Abstract: Growth and characterization of advanced group IV semiconductor materials with CMOS‐compatible applications are demonstrated, both in photonics. The investigated GeSn/SiGeSn heterostructures combine direct bandgap GeSn active layers with indirect gap ternary SiGeSn claddings, a design proven its worth already decades ago in the III–V material system. Different types of double heterostructures and multi‐quantum wells (MQWs) are epitaxially grown with varying well thicknesses and barriers. The retaining high material quality of those complex structures is probed by advanced characterization methods, such as atom probe tomography and dark‐field electron holography to extract composition parameters and strain, used further for band structure calculations. Special emphasis is put on the impact of carrier confinement and quantization effects, evaluated by photoluminescence and validated by theoretical calculations. As shown, particularly MQW heterostructures promise the highest potential for efficient next generation complementary metal‐oxide‐semiconductor (CMOS)‐compatible group IV lasers. Abstract : The formation of Si–Ge–Sn‐based direct bandgap group IV heterostructures proves to be a viable path toward highly efficient integrated light emitters. While GeSn/SiGeSn double heterostructures already show optically pumped lasing, additional benefits are expected in multi‐quantum well structures. Efficient separation of carriers from defects gives rise to considerably increased nonradiative carrier lifetimes in the latter.